Liquid‐Metal‐Enabled Mechanical‐Energy‐Induced CO2 Conversion. Issue 1 (21st October 2021) - Tang, Junma; Tang, Jianbo; Mayyas, Mohannad; Ghasemian, Mohammad B.; Sun, Jing; Rahim, Md Arifur; Yang, Jiong; Han, Jialuo; Lawes, Douglas J.; Jalili, Rouhollah; Daeneke, Torben; Saborio, Maricruz G.; et al.
Abstract: A green carbon capture and conversion technology offering scalability and economic viability for mitigating CO2 emissions is reported. The technology uses suspensions of gallium liquid metal to reduce CO2 into carbonaceous solid products and O2 at near room temperature. The nonpolar nature of the liquid gallium interface allows the solid products to instantaneously exfoliate, hence keeping active sites accessible. The solid co‐contributor of silver–gallium rods ensures a cyclic sustainable process. The overall process relies on mechanical energy as the input, which drives nano‐dimensional triboelectrochemical reactions. When a gallium/silver fluoride mix at 7:1 mass ratio is employed to create the reaction material, 92% efficiency is obtained at a remarkably low input energy of 230 kWh (excluding the energy used for dissolving CO2 ) for the capture and conversion of a tonne of CO2 . This green technology presents an economical solution for CO2 emissions. Abstract : With mechanical energy as the stimulus, CO2 is converted into solid carbon and O2 in a liquid‐metal‐based reaction system. Using the synergism of Ga nanodroplets and Ag–Ga nanorods, CO2 conversion proceeds through the triboelectrochemical reaction on Ga, while the Ag–Ga rods ensure the system's sustainability. This is achieved at a remarkably low energy consumption and high efficiency.